Public Diplomacy and Bilateral Relations Building: Options for National Economic Development in Nigeria - Afowowe, Oluranti (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The dynamics of globalization in the 21st century created inter-dependencies of nation-states that define the character, essence and relational complexities of the international community. Technological and scientific advancements, particularly in the last five decades, have redefined human existence and context of inter-states and inter-personal relations in a way that make the world, a global village. Interdependency of states had become phenomenal in the age of globalization. Action(s) and even inaction(s) of states have far reaching implications not only on socioeconomic development, but more significantly the security and continued corporate existence of Nation states. Understandably, therefore, states seek to sustain, advance, promote, defend and protect their self-defined interests (cultural, social, economic, political and security) within the context of the international community through the instrumentalities of violent (wars) and peaceful (diplomacy) mechanisms. Human history succinctly demonstrates that ultimate interests of states are better achieved through diplomacy that is cost effective and efficient rather than wars, particularly in modern age of sophisticated weapons (nuclear, biological and chemical) of mass destructions with capability of putting an end to human existence. The focal point of this study is to examine the different ramifications of public diplomacy as a veritable tool of achieving states’ objectives and interests, especially within the context of bilateral relations among comity of nations.